2014
DOI: 10.1590/s1516-35982014000600005
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance, composition and carcass yield of lambs treated with zeranol

Abstract: -Twenty weaned male hair lambs with average body live weight of 19.20 kg±2.18 kg (SD) were used to evaluate the effect of zeranol on growth, composition and carcass yield. The animals were distributed into a completely randomized design with two treatments: no anabolics (control); and treatment with zeranol, using a subcutaneous dose of 10 mg/50 kg body live weight. Lambs received a diet with 15 g/100 g of crude protein and 2.8 Mcal of metabolizable energy/kg dry matter for 84 days. At the end of experiment al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Although lambs implanted with 12 mg zeranol are more efficient in converting feed ( 4.62 kg/kg gain ) as compared with the control (5.77 kg/kg gain ) and lambs implanted with 24 mg zeranol ( 5.66 kg/kg gain ) however, it was impossible to analyze the date of feed efficiency statistically due to that lambs are fed as a group bases. Also, it have been reported by Landau et al, (1987), Castillo et al, (2014) and Alkass and Kak (2015), that implantation of lambs with zeranol had no effect on feed efficiency. The fattening period required by lambs to attain their prescribed slaughter weight (40kg) are not significantly different and averaged 61.62, 58.00 and 66.22 days for intact lambs, treated with 12mg ,24 mg zeranol, respectively.…”
Section: Results and Discussion Growth Performancementioning
confidence: 85%
See 2 more Smart Citations
“…Although lambs implanted with 12 mg zeranol are more efficient in converting feed ( 4.62 kg/kg gain ) as compared with the control (5.77 kg/kg gain ) and lambs implanted with 24 mg zeranol ( 5.66 kg/kg gain ) however, it was impossible to analyze the date of feed efficiency statistically due to that lambs are fed as a group bases. Also, it have been reported by Landau et al, (1987), Castillo et al, (2014) and Alkass and Kak (2015), that implantation of lambs with zeranol had no effect on feed efficiency. The fattening period required by lambs to attain their prescribed slaughter weight (40kg) are not significantly different and averaged 61.62, 58.00 and 66.22 days for intact lambs, treated with 12mg ,24 mg zeranol, respectively.…”
Section: Results and Discussion Growth Performancementioning
confidence: 85%
“…Similarly, Sharp and Dyer (1970) observed increased (P<0.05) percent body water and protein and decreased (p<0.05) percent body fat. However, other workers including Field et al (1993), Nasahlas et al 2002, Castillo et al (2014) and Alkass and Kak (2015) who observed minimal effects on carcass composition between lambs implanted with zeranol and control lambs. Table (2): Effect of Zeranol implantation on some carcass characteristics of Awassi lambs (mean ± s.e).…”
Section: Carcass Tissue Distributionmentioning
confidence: 92%
See 1 more Smart Citation
“…En el mercado existen anabólicos estrogénicos en soluciones oleosas (Zeranol) y androgénica de varios compuestos (Nandrolona + Trembolona + Boldenona) para ser administrados vía parenteral, lo cual facilita su uso. Sin embargo, la información científica sobre sus efectos en el desempeño productivo y económico es escasa e inconsistente (Solis et al, 2009;Castillo et al, 2014). Por lo anterior, el objetivo del estudio fue comparar el desempeño productivo y la rentabilidad de una engorda de corderos machos y hembras en confinamiento tratados con zeranol (ZL), andrógenos (AND) y ZL+AND.…”
unclassified